2020
DOI: 10.1103/physrevb.102.134432
|View full text |Cite
|
Sign up to set email alerts
|

Spin-orbit torque generation in NiFe/IrO2 bilayers

Abstract: 5d transition-metal oxides have a unique electronic structure dominated by strong spinorbit coupling and hence they can be an intriguing platform to explore spin-current physics. Here, we report on room-temperature generation of spin-orbit torque (SOT) from a conductive 5d iridium oxide IrO2. By measuring second harmonic Hall resistance of Ni81Fe19/IrO2 bilayers, we find both dampinglike and fieldlike SOTs. The former is larger than the latter, enabling an easier control of magnetization. We also observe that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…The improved conductivity and low roughness in the optimized polycrystalline films likely contributed to the high θ SH = 0.31, which is comparable to the crystalline film result in [205]. Using spin-torque generation in permalloy (Ni 81 Fe 19 )/IrO 2 bilayers and measuring second-harmonic Hall resistance, Ueda et al [143] reported an effective θ SH = +0.093 ± 0.003 and a spin-diffusion length = 1.7 ± 0.2 nm at 300 K. The work again shows that θ SH in IrO 2 is comparable to that in Pt and in fact 7x higher than that in elemental Ir. Furthermore, the same group studied a stacking-order effect, where the magnetic and spintransport properties for two distinct stacking configurations, i. Qiu et al deposited IrO 2 film on a Y 3 Fe 5 O 12 (YIG) film to form an all-oxide spintronics device for the observation of the spin Seebeck effect in the IrO 2 [216].…”
Section: Spin Transportmentioning
confidence: 83%
See 1 more Smart Citation
“…The improved conductivity and low roughness in the optimized polycrystalline films likely contributed to the high θ SH = 0.31, which is comparable to the crystalline film result in [205]. Using spin-torque generation in permalloy (Ni 81 Fe 19 )/IrO 2 bilayers and measuring second-harmonic Hall resistance, Ueda et al [143] reported an effective θ SH = +0.093 ± 0.003 and a spin-diffusion length = 1.7 ± 0.2 nm at 300 K. The work again shows that θ SH in IrO 2 is comparable to that in Pt and in fact 7x higher than that in elemental Ir. Furthermore, the same group studied a stacking-order effect, where the magnetic and spintransport properties for two distinct stacking configurations, i. Qiu et al deposited IrO 2 film on a Y 3 Fe 5 O 12 (YIG) film to form an all-oxide spintronics device for the observation of the spin Seebeck effect in the IrO 2 [216].…”
Section: Spin Transportmentioning
confidence: 83%
“…Epitaxial thin films were realized on singlecrystalline TiO 2 substrates either in a pure O 2 atmosphere [113] or in an O 2 /Ar gas mixture [139]. Heterostructures composed of spin-orbit-coupled IrO 2 and ferromagnetic permalloys, such as Ni 81 Fe 19 and Co 40 Fe 40 B 20 , were deposited in situ in DC or RF sputtering systems for spin transport studies [140][141][142][143][144]. The depositions were conducted either at room temperature followed by a post-annealing process [141] or directly at elevated temperatures [140,142].…”
Section: Sputtering Growthmentioning
confidence: 99%
“…This large spin Hall conductivity is also accompanied by a low conductivity, and thus the spin Hall angle still remains smaller than that of Pt and is of the order of θ SHE = 4%. Recent spin-torque measurements have however indicated a θ SHE = 9% 104 , with a spin diffustion length λ S =1.7 nm. Spin Seebeck measurements yielded a product θ SHE × λ S =0.15 nm, consistent with these results 105 .…”
Section: Ruthenates Iridates and Other Oxide Systemsmentioning
confidence: 98%
“…This DOI: 10.1002/aelm.202300666 interconversion, which lays the foundation for the generation, manipulation, and detection of spin-current, has been intensively studied in various types of materials including heavy metals, [2] topological insulators, [3,4] van der Waals materials, [5] etc. Recently, transition metal oxides, such as IrO 2 , [6][7][8][9][10] RuO 2 , [11,12] SrIrO 3 , [13][14][15][16][17][18][19][20][21][22] SrRuO 3 , [23][24][25][26] WO 2 , [27] and Pt oxide system, [28] have been demonstrated as another family of promising materials that exhibit large spin-to-charge conversion efficiency. [29,30] The investigation of spin and charge interconversion in oxides is largely spurred due to the high spin-to-charge conversion efficiency and the novel manipulation methods arising from the interplay of lattice, charge, spin, and orbital degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%